Unexpected Conduction Blocks in SORD ‐Related Distal Motor Neuropathy: A Case Report - Amiela Angeli Bucur; Gabriele Rodolico; Alessandra Tessa; Filippo Maria Santorelli; Martina Sperti; Deborah Leccese; Mario Maturo; Sabrina Matà (Clinical Case Reports, 2026)
ABSTRACT Distal weakness requires an extensive differential diagnosis. In this case, conduction blocks indicated multifocal motor neuropathy, but immunotherapy proved ineffective. Ultimately, genetic testing revealed a sorbitol dehydrogenase mutation, highlighting the importance of combining electrophysiological findings with molecular studies in cases where the diagnosis remains unclear.